2019
DOI: 10.3389/fimmu.2019.00071
|View full text |Cite
|
Sign up to set email alerts
|

Scoring System for Tumor-Infiltrating Lymphocytes and Its Prognostic Value for Gastric Cancer

Abstract: The tumor microenvironment (TME) is the internal environment of malignant tumor progression, and the host antitumor immune response and normal tissue destruction occur in the TME. Tumor-infiltrating lymphocytes (TIL) is a crucial component of the TME and reflect the host antitumor immune response. The purpose of this study was to discuss the methodology for TIL evaluation and assess the prognostic value of TIL in gastric cancer. In total, we reviewed 1,033 gastrectomy cases between 2002 and 2008 at the Third A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
103
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(109 citation statements)
references
References 37 publications
5
103
0
1
Order By: Relevance
“…Moreover, lymphocytes are usually recruited to the tumor microenvironment and engage in cell-mediated tumor responses. Numerous data have revealed that tumor infiltrating lymphocytes are associated with patient outcomes in various types of cancer [50][51][52][53][54], and lymphocyte phenotypes are fundamental for antitumor immunity and prognosis [38]. Therefore, reduced tumor infiltrating and peripheral lymphocytes might be indicative of impaired host antitumor response and favorable tumor microenvironments for cancer progression and dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, lymphocytes are usually recruited to the tumor microenvironment and engage in cell-mediated tumor responses. Numerous data have revealed that tumor infiltrating lymphocytes are associated with patient outcomes in various types of cancer [50][51][52][53][54], and lymphocyte phenotypes are fundamental for antitumor immunity and prognosis [38]. Therefore, reduced tumor infiltrating and peripheral lymphocytes might be indicative of impaired host antitumor response and favorable tumor microenvironments for cancer progression and dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with elevated FLR and poor prognosis, it is possible to select appropriate treatment methods based on the actual clinical conditions of the patients, such as consider the combined treatment of transarterial chemoembolization (TACE) + radiofrequency ablation (RFA) instead of surgical resection. 27 Furthermore, the application of different staging standards also has an impact on the prognosis of HCC patients. 28 The current international staging standards include Barcelona Clinic Liver Cancer (BCLC) staging system, Hong Kong Liver Cancer (HKLC) staging system, TNM staging system, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies describe a correlation between tumor size and tumorinfiltrating lymphocytes, with lower numbers of effector T cells in larger tumors. [87][88][89][90] In urothelial cancer, checkpoint inhibitors are registered as first-line treatment for patients who are cisplatin-ineligible and have high tumor PD-L1 expression, and as second-line treatment for patients who progressed on chemotherapy. A large, phase III trial is now investigating the role of avelumab as maintenance treatment following completion of first-line chemotherapy in urothelial cancer (NCT02603432).…”
Section: Combining Checkpoint Inhibitors With Cytoreductive Therapymentioning
confidence: 99%